Role of beneficial plants in improving performance of predators of oil palm bagworm - Jamian, Syari (2017)
The use of beneficial plants in the oil palm plantation is nature and food plant for insect predators widening year by year. This technique has been widely used in Malaysia. The effectiveness and advantages of this beneficial plant depends on several factors such as the presence of insects naturally, the existence of pests and abiotic factors. Research on the role of useful plants is critical to ensure and increase the effectiveness of natural enemies. The use of natural enemies as biological control agents against bagworms in palm plantation will be expanded. According to the Malaysian Palm Oil Board (MPOB), pest especially bagworms are becoming more common in Malaysia, still the effectiveness of the beneficial plants for protecting and food source for natural enemies in this country been carried out. In this study, the abundance and performance of predators against bagworm in palm plantations was done every month in three different oil palm fields. Sampling was performed using sweep nets of 30 cm diameter in three different localities; fields with cultivation of three beneficial plants namely Antigonon leptopus, Cassia cobanensis and Turnera subulata, single planting beneficial plants namely Turnera sp. and estate without beneficial plant. A total of 1,035 individuals of two species were found, namely Cosmolestes picticeps (n = 924) and Sycanus dichotomus (n = 111) both of Hemiptera order and Reduviidae family. They dominated the study areas that are practicing cultivation of three beneficial plants a significantly higher (F = 21.75; p <0.001) and (F = 32.21, p <0.001), compared to estate planting a single beneficial plant and without beneficial plant respectively. Fluctuations in insect predators correlated with rainfall and the presence of bagworm. Data showed that the sampling population, the adult insect predators found in the study area, with peaks identified particularly in May, June, July, September and October 2015 on estates that planting these three types of beneficial plants. Antigonon leptopus, Cassia cobanensis and Turnera subulata were the plants with potential to increase the number of predators in oil palm plantations. This was proved when bagworm outbreak incidences dropped on the planting of three species of beneficial plants than the other two regions. The population of predators, C. picticeps and S. dichotomus were not significantly correlated with rainfall parameters and bagworm. Studies showed that predation, tripled the number of bagworms where Metisa plana eaten by adults S. dichotomus compared to C. picticeps. Furthermore, the reaction function M. plana on different densities of 2, 4, 6, 8 and 10 S. dichotomus showed the reaction function of type II, with 1.9, 3.4, 5, 6.4 and 8.1 individually rate than 0.9, 1.4, 2.1,1.9 and 2.3 of predation by C. picticeps rates. Therefore, based on the results obtained in this study, predators S. dichotomus can be used to control bagworm. The results showed a large number of adult S. dichotomus attracted to useful plants namely, C. cobanensis and T. subulata compared than most other plants, A. leptopus, Asystasia intrusa, Euphorbia heterophylla and Ageratum conyzoides. The study of the nutrient content in the flower nectars and six plants was carried out using the GS-MS method. Results showed that all plants contained volatile composition to attract insect predators. For the review on the role of useful plants, T. subulata was tested on different combination treatments where the comparison with the existence of S. dichotomus, oil palm trees, bagworms and T. subulata were implemented. The insect predators need shelter and food sources such as nectar and honey for a longer life span. This was evident when the cage has only insect predators, palm trees and T. subulata. There was no significant difference between the cage with S. dichotomus, oil palm trees, T. subulata and M. plana, life span of S. dichotomus male and female (30.40 and 30.84 days) as compared to male and female (31.08 and 31.72 days) respectively. The cultivation of the suggested beneficial plant in oil palm to maintain the abundance of natural enemies to control pests of oil palm leaves is of major concern.